1998
DOI: 10.1063/1.122630
|View full text |Cite
|
Sign up to set email alerts
|

Quasi-ideal strontium titanate crystal surfaces through formation of strontium hydroxide

Abstract: In recent years, well-defined and nearly perfect single crystal surfaces of oxide perovskites have become increasingly important. A single terminated surface is a prerequisite for reproducible thin film growth and fundamental growth studies. In this work, atomic and lateral force microscopy have been used to display different terminations of SrTiO3. We observe hydroxylation of the topmost SrO layer after immersion of SrTiO3 in water, which is used to enhance the etch-selectivity of SrO relative to TiO2 in a bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
594
0
1

Year Published

2002
2002
2019
2019

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 718 publications
(605 citation statements)
references
References 12 publications
(2 reference statements)
10
594
0
1
Order By: Relevance
“…The substrate-surface treatment followed the procedure outlined by Koster et al 24 The PTO thin films were grown at 570°C using reflection high-energy electron diffraction assisted pulsed-laser deposition ͑KrF excimer laser of = 248 nm͒. A laser spot size of 2.5 mm 2 with an energy density of 2 J / cm 2 at an oxygen background pressure of 0.13 mbar was used, and the substrate-target distance was kept between 48 and 51 mm.…”
Section: Methodsmentioning
confidence: 99%
“…The substrate-surface treatment followed the procedure outlined by Koster et al 24 The PTO thin films were grown at 570°C using reflection high-energy electron diffraction assisted pulsed-laser deposition ͑KrF excimer laser of = 248 nm͒. A laser spot size of 2.5 mm 2 with an energy density of 2 J / cm 2 at an oxygen background pressure of 0.13 mbar was used, and the substrate-target distance was kept between 48 and 51 mm.…”
Section: Methodsmentioning
confidence: 99%
“…Kawasaki et al [24] and later-on Koster et al [25] used a combination of chemical etching and oxygen post annealing to realize perfectly single-terminated STO (001) substrates [ Fig.2c]. Later studies demonstrated that these single crystals were TiO 2 -terminated and structurally unreconstructed [26]; this is at odds with several previous surface studies on ultra high vacuum (UHV) prepared STO single crystals, which exhibited a wide range of reconstructions, like 2x1, 2x2, c2x2 and √5x √5-R26.6° [27], depending essentially on the annealing temperatures in UHV…”
Section: General Properties Of Laalo 3 and Srtiomentioning
confidence: 99%
“…Каналовые спектры MEIS, полученные для гетероструктур LAO/STO с толщиной слоя LAO в 1 и 3 u. c., показаны на рис. Отметим, что блочный характер структуры подложки STO, неоднородные механические напряжения, наличие на свободной поверхности титаната стронция участков, покрытых двухслойными пакетами TiO 2 [6] и карбонатом стронция (SrCO 3 [7]), могут влиять на интенсивность катионных замещений в области межфазной границы между слоем LAO и подложкой STO и, как следствие, глубина проникновения атомов лантана в подложку на различных участках последней не является одинаковой, а латерально варьируется.…”
Section: экспериментunclassified